PENATALAKSANAAN FISIOTERAPI PADA KASUS LUKA BAKAR GRADE 2-3 BILATERAL TANGAN DENGAN MODALITAS EXERCISE PADA ANAK USIA 12 TAHUN - Sjafarial, Ilham (Jurnal Kesehatan An-Nuur, 2026)
Burns are traumatic injuries that frequently occur in children with significant impact on hand function. Grade 2-3 burns on bilateral hands can cause severe pain, limitation of range of motion (ROM), decreased muscle strength, edema, and impairment of daily functional activities. To determine the effectiveness of physiotherapy management with exercise modalities on pain reduction, ROM improvement, edema reduction, muscle strength enhancement, and functional ability in a case of bilateral grade 2-3 hand burns in a 12-year-old child. This study employed a case study method with a pre-post intervention design on one 12-year-old male patient diagnosed with grade 2-3 burns on both hands (4% total body surface area). Physiotherapy intervention was conducted for 6 treatment sessions following the wound healing phases (acute inflammation, transition, and early proliferation) with a program comprising: continuous elevation, positioning, passive range of motion (PROM), active-assisted range of motion (AAROM), massage, circulation exercises, isometric exercises, and functional training. Measured parameters included: pain (VAS), wrist and finger ROM (goniometer), muscle strength (MMT), edema (circumferential measurement), and functional ability (Barthel Index). After 6 treatment sessions, significant improvements were observed in all parameters. Resting pain decreased from VAS 8/10 to 4/10 (50% reduction), pain with movement from 9/10 to 6/10 (33.3% reduction). Wrist ROM showed improvement: right dorsiflexion- palmarflexion from 15°-0-20° to 35°-0-40° (133% and 100% increase), left from 20°-0-25° to 40°-0-45° (100% and 80% increase). MCP ROM increased 10°, PIP 10°, and DIP 5° bilaterally. Muscle strength for grip improved from unmeasurable to 2+/5, pinch strength to 2+/5 (right) and 3-/5 (left), wrist muscles from 2/5 to 3/5. Edema reduced by 0.9 cm (right) and 1 cm (left). Barthel Index increased from 70 to 85 (21.4% improvement). Physiotherapy management with exercise modalities adapted to wound healing phases is effective in reducing pain, improving ROM, decreasing edema, enhancing muscle strength, and improving functional ability in a case of bilateral grade 2-3 hand burns in a child. A comprehensive and progressive therapy program is crucial to prevent long-term complications such as contractures and hand function impairment.